Case Report: Effective management of a Meige syndrome patient with subthalamic stimulation-induced dyskinesia through timed stimulation programming of different contacts - Meng, Dawei; Sun, Haihang; Wang, Ning; Fu, Zonghui; Wang, Lin (Frontiers in Human Neuroscience, 2026)
IntroductionMeige syndrome is a rare adult-onset segmental dystonia characterized by blepharospasms and oromandibular dystonia. Deep brain stimulation (DBS) of the subthalamic nucleus (STN) is an established treatment, but it can lead to stimulation-induced dyskinesia (SID) in some patients. Refractory SID in Meige syndrome after STN-DBS is clinically challenging. We report a case of a Meige syndrome patient who developed refractory SID following STN-DBS and was successfully managed using a novel timed-stimulation programming strategy employing different contacts.Case descriptionA 47-year-old female with a two-year history of Meige syndrome developed refractory SID after the treatment of STN-DBS. Various programming strategies were attempted, including monopolar stimulation, interleaved stimulation, bipolar stimulation et al., but none achieved a balance between symptom control and SID. A novel approach involving timed alternation between ventral contacts (contacts 3 and 7) and dorsal contacts (contacts 4 and 8) was implemented. The stimulation was gradually programmed, the duration of ventral stimulation was increased while decreasing dorsal stimulation. Eventually, the patient achieved significant symptom improvement without SID. The reconstruction of the volume of tissue activated (VTA) revealed that this stimulation strategy likely modulates the neural circuits of pallidothalamic fibers (PTF) to suppress SID.ConclusionThis case demonstrates that this noval timed stimulation programming can effectively manage refractory SID in Meige syndrome patients, offering a viable alternative when conventional methods fail. The findings suggest that PTF stimulation plays a key role in SID suppression, and this strategy warrants further investigation in larger cohorts.